The projected numbers of degenerative spine disease in Austria from 2017 to 2080: a perspective-based scenario analysis - Hitzl, Wolfgang; Schwartz, Christoph; Zausinger, Stefan; Winkler, Peter A.; Ladisich, Barbara; Schöffski, Oliver; Romagna, Alexander (Journal of Neurosurgical Sciences, 2023)
BACKGROUND: Spinal surgery has to address the challenge of a dramatic increase of the growing number of older persons. The purpose of the present study was to project the numbers of surgically treated degenerative spine disease (DSD) in Austria from 2017 until 2080 to provide potential future scenarios that the Austrian Health system might have to face. METHODS: Current numbers on demographic information from Austria as well as population projections for 2017-2080 were obtained from Statistics Austria (STAT). A lower/main/upper scenario reflecting low/main/high growth and ageing scenarios deducted from fertility, life expectancy and immigration calculations was used. Information on prevalence of surgically treated DSD was obtained from the Austrian Spine Register. RESULTS: The population in Austria (evaluated in 2017) was 8.78 millions and is estimated to evolve to 7.86/10.0/13.1 millions by 2080. The total number of surgically treated DSD recorded in the Spine Register was 9300 and was estimated to be 9300/11200/13700 in 2080. The number of subjects with surgically treated DSD were expected to increase in the age-strata (main scenario), 100% corresponds to the number in each age and gender stratum: 0-40 years by (male/female) 2%/2%, 40-50 years -7%/-7%, 50-59 years -11%/-9%, 60-69 years 21%/16%, 70-79 years 51%/31%, 80-89 years 211%/129% and 90+years 698%/411%. CONCLUSIONS: Total numbers of subjects with DSD in Austria will increase from 2017 to 2080. The increase will be substantial in those aged 80+ and those aged 90+. The assumptions of this analysis were taken conservatively. Hence, the future socio-economic burden to society might be greater as projected by the study.
CRIS-Team Scopus Importer:2023-07-07